2021
DOI: 10.1016/j.ejso.2020.11.137
|View full text |Cite
|
Sign up to set email alerts
|

Treatment strategies and clinical outcomes in consecutive patients with locally advanced pancreatic cancer: A multicenter prospective cohort

Abstract: Introduction: Since current studies on locally advanced pancreatic cancer (LAPC) mainly report from single, high-volume centers, it is unclear if outcomes can be translated to daily clinical practice. This study provides treatment strategies and clinical outcomes within a multicenter cohort of unselected patients with LAPC. Materials and methods: Consecutive patients with LAPC according to Dutch Pancreatic Cancer Group criteria, were prospectively included in 14 centers from April 2015 until December 2017. A c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 27 publications
(34 reference statements)
0
23
0
Order By: Relevance
“…The median progression-free survival (PFS) of patients with MPC receiving FOLFIRINOX or GnP as the first-line chemotherapy ranged from 5.5 to 6.4 months (4,5). The median PFS of patients with LAPC receiving FOLFIRINOX or GnP ranged from 7 to 8 months (11). Compared with the aforementioned previous studies (4,5,11), the median PFS in our study was 6.4 months; longer PFS and shorter PFS were defined as PFS ≥7 months and PFS <7 months, respectively.…”
Section: Definitionmentioning
confidence: 49%
See 1 more Smart Citation
“…The median progression-free survival (PFS) of patients with MPC receiving FOLFIRINOX or GnP as the first-line chemotherapy ranged from 5.5 to 6.4 months (4,5). The median PFS of patients with LAPC receiving FOLFIRINOX or GnP ranged from 7 to 8 months (11). Compared with the aforementioned previous studies (4,5,11), the median PFS in our study was 6.4 months; longer PFS and shorter PFS were defined as PFS ≥7 months and PFS <7 months, respectively.…”
Section: Definitionmentioning
confidence: 49%
“…The median PFS of patients with LAPC receiving FOLFIRINOX or GnP ranged from 7 to 8 months (11). Compared with the aforementioned previous studies (4,5,11), the median PFS in our study was 6.4 months; longer PFS and shorter PFS were defined as PFS ≥7 months and PFS <7 months, respectively. Disease progression was assessed using the Response Evaluation Criteria in Solid Tumors, version 1.1 (12).…”
Section: Definitionmentioning
confidence: 49%
“…A recent observational study including 680 consecutive patients with borderline resectable and LAPC showed a median overall survival of 13 months for all patients after an intention-to-treat analysis [45]. Recent multicenter data from The Netherlands showed a median overall survival of 14 months for patients with LAPC treated with FOLFIRI-NOX [46]. These studies likely better reflect "real-world" data, and the assumption of 14.1 months can be preserved with these data.…”
Section: Discussionmentioning
confidence: 97%
“…The prognosis of patients with inoperable pancreatic ductal adenocarcinoma (PDAC) is dismal despite substantial efforts to meaningfully improve outcomes (1). Over the last decade, modest gains have been realized by intensifying chemotherapy although long-term local control (LC) and overall survival (OS) are rarely achieved (2)(3)(4). Conversely, significantly escalating radiation therapy (RT) to an ablative dose has not been considered feasible for most patients using conventional image guidance because of interfraction anatomic changes and uncertainty in assuring that dose to nearby organs at risk (OARs) is safe prior to delivering each fraction (5).…”
Section: Introductionmentioning
confidence: 99%